1995
DOI: 10.1117/12.205988
|View full text |Cite
|
Sign up to set email alerts
|

<title>Photothermal microscopy for cell imaging and diagnostics</title>

Abstract: Dual-laser photothermal (PT) techniques are applied for a live blood cell studies. The measurement of the action of a pump pulse (400-600 nm, 10 ns, 1-500 pJ) on a single cell provides the imaging of cell's absorbing structure/thermal field, spectroscopy and control of cell's state.The imaging technique includes acquisition of three types of images: optical image, pulsed laser image with 5 ns temporal resolution and PT-image with the same temporal and 0.5 jim spatial resolution. In PT-images of WBC the details… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 1 publication
(2 reference statements)
2
8
0
Order By: Relevance
“…Such load has thermal and mechanical origin due to light absorption by natural cell chromophores. With optical noninvasive registration of cell response we come to the idea of photothermal cytometry ' S. 9 -RBC in functional terms has limited ability to restore its structure, to maintain energy balance and ion transport through the membrane. Besides RBC does not produce proteins neither incorporates DNA and therefore is considered to be rather stable and predictable cell.…”
Section: Introductionmentioning
confidence: 99%
“…Such load has thermal and mechanical origin due to light absorption by natural cell chromophores. With optical noninvasive registration of cell response we come to the idea of photothermal cytometry ' S. 9 -RBC in functional terms has limited ability to restore its structure, to maintain energy balance and ion transport through the membrane. Besides RBC does not produce proteins neither incorporates DNA and therefore is considered to be rather stable and predictable cell.…”
Section: Introductionmentioning
confidence: 99%
“…[47][48][49][50][51][52][53][54][55][56][57] PTI is based on irradiating cells with a focused short-pulse pump laser and recording the temperature-dependent variations of the refractive index with phase-contrast imaging of a second collinear laser pulse. It was shown that PT response from different cells is sensitive to different environmental impact including temperature, chemicals, and drugs.…”
Section: Introductionmentioning
confidence: 99%
“…However to date a little progress has been made in biological applications, and no results have been reported for imaging of single live cells. The PTI is new modification of calorimetric technique and is based on combination of laser PT dual beam time-resolved technique and phase-contrast microscopy [28][29][30][31][32][33][34][35]. This paper is focused on discussion of PTI features for single live cells studies through visualization of laser-induced local thermal effects.…”
Section: Introductionmentioning
confidence: 99%